P252 Clinical profile of infants with cystic fibrosis screen positive, inconclusive diagnosis (cfspid) in the west midlands. (15th November 2017) - Ali, SH; Clarke, J; Rao, S; Desai, M; Nagakumar, P
Abstract : Background: The introduction of newborn screening for cystic fibrosis (CF) has resulted in up to 10% of infants with the positive result but inconclusive diagnosis. The European cystic fibrosis consensus group has defined CFSPID as newborn screened infants with elevated immunoreactive trypsinogen and normal sweat chloride and two CFTR mutations, at least one with unclear phenotypical consequences OR infants with intermediate sweat chloride with one or no CFTR mutations (Munck:2015). The majority will remain well and have no long-term health implications. However, a small percentage of these infants may develop the disease by three years. Aim: To study the prevalence, clinical characteristics and clinical course of children who meet the CFSPID criteria within a large UK regional paediatric CF centre Methods: Retrospective data review of children identified on newborn screening who met the ECFS CFSPID criteria using CF registry, regional screening centre notification and the local network database. Results: Between October 2006 to December 2016, 148 infants were CF screen positive. 9 children (6.08%) met CFSPID diagnostic criteria. The median follow up period was 25 months (range 6–95 months). Median age at repeat sweat test was 3 years (range 1.5–5 year). All patients were heterozygous for ΔF508. The second mutation identified included R117H in 6 children, D1152H in one child and Arg810Ser in 2 siblings. 2 patients had Staph aureus and Haemophilus influenzae once on cough swabs. None of them was positive for Pseudomonas aeruginosa . All were pancreatic sufficient. All children in the group remained nutritionally well. None had chronic isolates of significant respiratory pathogens common in cystic fibrosis and repeat sweat test remained normal in all patients. Conclusion: Early outcomes for CFSPID are good. National guidance on information provided to families at diagnosis, frequencies of clinic follow up are necessary. In addition assessment of the psychological impact of the diagnosis to the families would be valuable. National data collection possibly through a UK CF registry based study to inform long term outcomes in children with a diagnosis of CF SPID is needed.